Development of a composite based on polylactic acid and lignocellulosic waste: new packaging for meat food storage - Muñoz-Pabon, Karen Sofia; Castillo, Héctor Samuel Villada; Concha, José Luis Hoyos; Ayala Aponte, Alfredo A.; Solanilla Duque, José Fernando (Frontiers in Sustainable Food Systems, 2023)
Pursuing new packaging that contributes to the safety of meat products, that can also be from renewable sources and that has adequate mechanical properties is a challenge. Therefore, this study attempted to incorporate a layer of polylactic acid (PLA) containing nisin and oregano oil extract (OEO) into biocomposites of cassava bran (CB) and coffee husk (CH) to improve their mechanical properties and enhance their antimicrobial properties. A compression molding process is carried out, the operating conditions for the preparation of the biocomposite were pressure: 40 bar, temperature: 170°C, and time: 2.5 min. The composition of the biocomposite was 80, 18, and 2% of CB, CH, and glycerol respectively, with 30% moisture. The polylactic acid (PLA) layer was added by immersion and contained nisaplin and OEO. PLA layer was evaporated in forced convection oven. Once the active packaging was obtained, inhibition in vitro against Listeria monocytogenes was performed. The packing containing OEO and nisin that showed the highest inhibition on the pathogen was used for stability analysis in pork. In order to measure changes in pork meat quality, the biocomposite with and without coating and with commercial polystyrene packaging were compared. Raw meat muscle was kept at 4° C and was tested for color, pH, moisture, and texture profile analysis (TPA) for 0, 7, 14, and 21 days. The values of the flexural test of the biocomposite were: 11.08 MPa of maximum flexural strength (σF), 1.81% of maximum deformation (εF), and 842.22 MPa of elastic modulus (EM). According to the results of in vitro inhibition, the packaging can contribute to reduce the proliferation of gram-positive microorganisms, such as L. monocytogenes. During storage, the hardness and gumminess of the meat showed significant changes, mainly in the PLA-free biocomposite. Results on pork meat showed that packaging with antimicrobials and PLA can maintain color, texture, moisture, and pH similar to commercial packaging.